Thai herbal antipyretic 22 formula (APF22) inhibits UVA‐mediated melanogenesis through activation of Nrf2‐regulated antioxidant defense. (19th April 2018) - Onkoksoong, Tasanee; Jeayeng, Saowanee; Poungvarin, Naravat; Limsaengurai, Saowalak; Thamsermsang, Onusa; Tripatara, Pinpat; Akarasereenont, Pravit; Panich, Uraiwan
Abstract : Thai herbal antipyretic 22 formula (APF22), a polyherbal formula, has been traditionally used to treat dermatologic problems including hyperpigmentation. Exposure of the skin to ultraviolet A (UVA) causes abnormal melanin production induced by photooxidative stress. This study thus aimed to investigate the protective effects of APF22 extracts and phenolic compounds, ferulic acid (FA), and gallic acid (GA; used as positive control and reference compounds), on melanogenesis through modulation of nuclear factor E2‐related factor 2 (Nrf2) signaling and antioxidant defenses in mouse melanoma (B16F10) cells exposed to UVA. Our results revealed that the APF22 extracts, FA, and GA reduced melanin synthesis as well as activity and protein levels of tyrosinase in UVA‐irradiated B16F10 cells. Moreover, APF22 extracts and both FA and GA were able to activate Nrf2‐antioxidant response element signaling and promote antioxidant defenses including glutathione, catalase, glutathione peroxidase, and the glutathione‐S‐transferase at both mRNA and enzyme activity levels in irradiated cells. In conclusion, APF22 extracts suppressed UVA‐mediated melanogenesis in B16F10 cells possibly via redox mechanisms involving activation of Nrf2 signaling and upregulation of antioxidant defenses. Moreover, pharmacological action of the APF22 extracts may be attributed to the phenolic compounds, FA, and GA, probably serving as the APF22's active compounds.